The affecting factors of childbirth fear for pregnant women admitted to a health center and university hospital in Turkey - Didem Kaya; Funda Evcili (Journal of Health Research, 2020)
Purpose – Fear of birth may cause perinatal complication, increased risk of intervention and need for analgesia, delayed mother–infant attachment process and deterioration of spouse relationship. The purpose of this study was to determine the affecting factors and childbirth fears of Turkish pregnant women. Design/methodology/approach – This is a descriptive research type. The sample of this study consisted of 78 pregnant women who met the inclusion criteria and agreed to participate in this study. This study was carried out in a family health center and university hospital in a city in Turkey. Data were collected with Personal Information Form and Wijma Expectancy/Experience Scale-A Version (W-DEQ A). Findings – The mean scores of pregnant women from W-DEQ A version were 75.60 ± 9.48. In 65.4% of pregnant women, fear of severe birth, 20.5% fear of clinical birth and 14.1% of children had a fear of moderate birth. W-DEQ A version, the third trimester, unplanned pregnancies, lack of knowledge of the level of inadequate birth and more than eight pregnancies in pregnancy, the total score of pregnant women was found to be higher (p < 0.05). Research limitations/implications – The limitation of this study is its small sample size. Further studies with larger sample sizes are needed. Practical implications – It was determined that one-fifth of the sample group experienced birth fear at the clinical level and childbirth fear level is associated with unplanned pregnancies, lack of knowledge. In antenatal period, the pregnant woman should be encouraged to express her feelings and thoughts about the labor and give information about the labor. Social implications – Cognitive and behavioral education programs can be structured to cope with fear of birth for pregnant women at risk. Originality/value – This research is original. This study presents data on Turkish women. The data can also be used to evaluate intercultural differences.